DISKURSUS DERADIKALISASI AGAMA: POLA RESISTENSI PESANTREN TERHADAP GERAKAN RADIKAL - Hasyim Muhammad; Khoirul Anwar; Misbah Zulfa Elizabeth (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
Pesantren had a specific perspective related to religious radicalism and violence. The purpose of this study is to uncover the discourse of radicalism and de-radicalization in Pesantren Soko Tunggal Semarang. Applying the qualitative research, it was revealed that Pesantren Soko Tunggal against all forms of violence in the name of religion. According to Pesantren Soko Tunggal radical movements in the name of religion is a form of misunderstanding of the religion. Islamic radicalism is generally based on the Wahhabi’s understanding, so that attitudes and behavior are influenced by the teachings of Wahhabi. In the view of Wahabism heresy in religion is a form of desecration and denial that must be fought. Pesantren assumed that Pancasila and UUD 1945 is a form of actual enforcement of Islamic law due to Pesantren Soko Tunggal kept to preserve the values of moderatism and develop a peaceful multicultural life.